2015
DOI: 10.1177/0300060515587576
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear expression and clinical significance of phosphohistidine phosphatase 1 in clear-cell renal cell carcinoma

Abstract: Objective: To explore expression and clinical relevance of phosphohistidine phosphatase 1 (PHPT1) in clear-cell renal cell carcinoma. Methods: Patients with clear-cell renal cell carcinoma who underwent radical or nephron-sparing nephrectomy were enrolled. Correlations between PHPT1 expression and demographic and clinical characteristics were analysed prospectively. Results: In total, 122 patients (78 male/44 female) were included. In normal kidney tissue, PHPT1 expression was observed only in the proximal tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Recently, a novel family of phosphatases has been identified that lends itself to the dephosphorylation of phosphohistidine residues [6]. This phosphatase is not well studied yet but seems to play a vital role in some cancers as well as insulin signaling [7], [8], [9]…”
Section: Protein Phosphatasesmentioning
confidence: 99%
“…Recently, a novel family of phosphatases has been identified that lends itself to the dephosphorylation of phosphohistidine residues [6]. This phosphatase is not well studied yet but seems to play a vital role in some cancers as well as insulin signaling [7], [8], [9]…”
Section: Protein Phosphatasesmentioning
confidence: 99%
“…Until recently, phosphorylation of the hydroxyl‐containing amino acids serine (Ser), threonine (Thr) and tyrosine (Tyr) was thought to be the primary mode of phosphorylation‐mediated signalling in non‐plant eukaryotes. However, a growing body of evidence (Besant & Attwood, ; Fan et al , ; Fraczyk et al , ; Fuhs et al , ; Shen et al , ; Wieland & Attwood, ; Panda et al , ; Srivastava et al , ; Xu et al , ,b; Fuhs & Hunter, ) indicates that phosphorylation of other amino acids, termed here “non‐canonical” phosphorylation, including His, Asp, Glu, Lys, Arg and Cys [in addition to pyrophosphorylation of Ser and Thr to form ppSer and ppThr (Chanduri et al , ; Harmel & Fiedler, ), and Lys polyphosphorylation (Bentley‐DeSousa & Downey, )], may also regulate protein signalling functions. Of note, the generation of both site‐specific and generic antibodies against phosphohistidine (pHis) (Kee et al , , ; Fuhs et al , ; Lilley et al , ) has recently allowed mammalian cell‐type independent roles for this PTM to be elucidated (Fuhs et al , ) in processes as diverse as ion channel regulation (Srivastava et al , ) and T‐cell signalling (Panda et al , ), and during cell proliferation, differentiation and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, phosphorylation of the hydroxyl-containing amino acids serine (Ser), threonine (Thr) and tyrosine (Tyr) was thought to be the primary mode of phosphorylation-mediated signalling in non-plant eukaryotes. However, a growing body of evidence [3][4][5][6][7][8][9][10][11][12][13] indicates that phosphorylation on the imidazolecontaining amino acid histidine (His) also plays a significant, but ill-defined, role in human biology. In contrast, and despite occasional reports in the literature 14,15 , the prevalence (or otherwise) of noncanonical amino acid phosphorylation on the five amino acids for which protein phosphorylation is chemically feasible (Asp, Arg, Lys, Glu, Cys) has yet to be revealed in human cells.…”
Section: Introductionmentioning
confidence: 99%